2019
DOI: 10.1007/s40201-018-00332-z
|View full text |Cite
|
Sign up to set email alerts
|

Arsenate removal from aqueous solutions using micellar-enhanced ultrafiltration

Abstract: In this study, arsenate (As-V) removal using micellar enhanced ultrafiltration (MEUF) modified by cationic surfactants was studied by a dead-end polyacrylonitrile (PAN) membrane apparatus. The UF membrane has been produced by a phase inversion process. The prepared membrane was characterized and analyzed for morphology and membrane properties. The influence of operating parameters such as initial concentrations of As-V, surfactants, pH, membrane thickness, and co-existing anions on the removal of As-V, surfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Their production and extraction methods are continually being optimized to increase efficiency and reduce costs, contributing to a more sustainable and circular economy. Further research is needed to optimize production, develop new formulations, and evaluate their long-term environmental impact [66] that have area of application not only for waste water but sea water also [67].…”
Section: Biosurfactants Instead Of Chemical Surfactantsmentioning
confidence: 99%
“…Their production and extraction methods are continually being optimized to increase efficiency and reduce costs, contributing to a more sustainable and circular economy. Further research is needed to optimize production, develop new formulations, and evaluate their long-term environmental impact [66] that have area of application not only for waste water but sea water also [67].…”
Section: Biosurfactants Instead Of Chemical Surfactantsmentioning
confidence: 99%
“…distribution in the aqueous and the micellar phases. Bahmani et al [80,81] reported that micelles composed of CPC resulted in higher arsenic removal (91.7%) compared to CTAB micelles (83.7%), and an increasing removal of both As (V) and NO 3as the CPC concentration was increased, however with an associated decrease in permeate flux.…”
Section: Arsenic (V) Removalmentioning
confidence: 99%
“…Currently, different methods with varying degrees of sophistication have been applied for As removal, including filtration, [ 10 ] precipitation, [ 11 ] ion exchange, [ 12 ] electrocoagulation, [ 13 ] biological processes, [ 14 ] membrane separation, [ 15 ] adsorption, [ 16 ] among others. It is important to note that if the removal of As(V) negatively charged species is challenging by itself, the development of technical approaches to retain the As(III) neutral forms is even more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…[8] The predominance of each arsenic form is dependent on water properties, such as pH and oxidation/reduction potential, but in the most usual conditions found in surface and underground water, As(V) is found as negative oxyanions (i.e., H 2 ) in oxidative conditions, while As(III) is stabilized as the neutral H 3 AsO 3 form in water environments with low oxygen content. [9] Currently, different methods with varying degrees of sophistication have been applied for As removal, including filtration, [10] precipitation, [11] ion exchange, [12] electrocoagulation, [13] biological processes, [14] membrane separation, [15] adsorption, [16] among others. It is important to note that if the removal of As(V) negatively charged species is challenging by itself, the development of technical approaches to retain the As(III) neutral forms is even more difficult.…”
Section: Introductionmentioning
confidence: 99%